Strategi Peningkatan Kualitas Pendidikan di SDN Lancong Kecamatan Sungai Mas Kabupaten Aceh Barat - Unio Resi; Agatha Debby Reiza Macella (Indonesian Journal of Teaching and Teacher Education, 2022)
Knowing the role of school supervisors and knowing the causes of the low quality of education at SDN Lancong, Sungai Mas District as the purpose of this study. In accordance with Government Number 25 of 2000 concerning Central and Provincial Authorities as autonomous regions, it has prompted major changes in the education management sistem in Indonesia, one of which is at SDN Lancong. The causes of the low quality of education are 4 factors at SDN Lancong with a fishbone diagram, including: 1) Human/HR; 2) Environment; 3) Method; 4) Material. The results of the analysis carried out by strategies to improve the quality of education at SDN Lancong include the role of supervisors who understand their main duties and functions, hold an interesting learning sistem with technology media in increasing interest in learning and every month a learning evaluation is carried out, besides using a clean room. and convenient for students to study, repair or buy learning tools with technological advances such as using infocus, as well as facilitating Lancong Elementary School with Wi-Fi. Next Conduct special training for teachers and school supervisors for the development of creative and innovative learning methods in teaching. In addition, there is a need for further socialization or teaching training according to the 2013 curriculum which is applied with appropriate learning time arrangements, besides being able to use learning with teaching aid technology